2009
DOI: 10.1073/pnas.0902859106
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB2 coordinates the formation of a morphological boundary and cell epithelialization during somite segmentation

Abstract: During early morphogenesis, tissue segregation is often accompanied by changes in cell shape. To understand how such coordination is regulated, somitogenesis was used as a model. When a somite forms in the anterior end of the presomitic mesoderm, an intersomitic boundary (gap) emerges, and it is rapidly followed by cell epithelialization at this border. It has been known that the gap formation is regulated by intercellular signals. We here demonstrate that cMeso-1, the chicken homolog of mouse Mesp2, upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 33 publications
0
98
0
Order By: Relevance
“…Gamma correction1.45 in A,C. Scale bars: 200m in A,B; 100m in C. (Durbin et al, 1998;Watanabe et al, 2009), hindbrain (Cooke et al, 2001;Cooke et al, 2005;Kemp et al, 2009) and skull (Twigg et al, 2004;Merrill et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma correction1.45 in A,C. Scale bars: 200m in A,B; 100m in C. (Durbin et al, 1998;Watanabe et al, 2009), hindbrain (Cooke et al, 2001;Cooke et al, 2005;Kemp et al, 2009) and skull (Twigg et al, 2004;Merrill et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, differentiating muscle satellite cells orient according to ephrin patterning Ephrin/Eph signaling is largely dependent on cell-cell contacts in order to create change in the directionality of a migrating cell; however, ephrin/Eph signaling also plays an important role in cellular segregation and patterning, as seen in the developing somite (Durbin et al, 1998;Watanabe et al, 2009) or the late embryonic forelimb (Swartz et al, 2001;Wada et al, 2003). We observed that elongated, possibly differentiating, satellite cells in the forelimb were uniformly oriented with respect to the axis of the stream exiting the limb bud (Fig.…”
Section: Research Article Satellite Cell Guidancementioning
confidence: 99%
“…S10). Expression of ephrin B2 (Efnb2), which encodes a known ligand of EphA4 signaling (Watanabe et al, 2009), was found in the caudal ND and the cloaca as well as in the pericloacal mesenchyme from E10.5 until E14.5 (Fig. 7C-F).…”
Section: Cellular Changes In the Distal Nd Of Dko Embryosmentioning
confidence: 99%
“…Intriguingly, reverse ephrin B2 signaling has been implicated in the control of epithelial cell adhesion in urorectal maturation by promoting tubularization of the urethra and septation of the urinary and the anorectal system (Dravis et al, 2004). Fifth, although EphA receptors preferentially bind to ephrin A ligands, ephrin B2 has been described as a ligand for EphA4 in some contexts (Watanabe et al, 2009); ephrin B2 binding to EphA7 still needs to be validated on the biochemical level. Last, and most importantly, conditional deletion of Efnb2 in the ND phenocopied the urinary tract defects of DKO embryos to a substantial extent, including blind or ectopically ending ureters, delayed CND removal, lack or delayed ND insertion and downregulation of Gata3/Lhx1/Ret in the caudal ND.…”
Section: Pax2(85)-cre;efnb2mentioning
confidence: 99%
“…Recently, we and others have suggested that the Mesp2 downstream events, such as the activation of ephrin-EphA4 signaling and the formation of a Tbx6 protein boundary, were more important for segmental border formation (Watanabe et al, 2009;Oginuma et al, 2008;Nakajima et al, 2006). In Lfng -/-embryos, the expression of EphA4 and the Tbx6 protein boundary were found to be diffuse or randomized (Fig.…”
Section: Research Articlementioning
confidence: 99%